Geriatric Assessment in Older Adults with Multiple Myeloma. Issue 5 (13th December 2018) - Wildes, Tanya M.; Tuchman, Sascha A.; Klepin, Heidi D.; Mikhael, Joseph; Trinkaus, Kathryn; Stockerl‐Goldstein, Keith; Vij, Ravi; Colditz, Graham
Abstract : BACKGROUND/OBJECTIVES: The incidence of myeloma in older adults is increasing, yet little is known about geriatric impairments in these patients. We aimed to examine the prevalence of geriatric impairments in older adults with myeloma and the association between geriatric assessment and autologous stem cell transplant eligibility. DESIGN: Prospective cohort study. SETTING: Two academic medical centers. PARTICIPANTS: A total of 40 adults 65 years and older with newly diagnosed myeloma were enrolled. MEASUREMENT: Participants completed a primarily self‐administered geriatric assessment, including measures of functional status, comorbidities, polypharmacy, psychosocial status, social support, quality of life, cognition, and physical performance. Outcomes were autologous stem cell transplant eligibility and receipt. RESULTS: Forty patients enrolled; their mean age was 71 years. Geriatric impairments were common: 62% reported dependence in one or more instrumental activities of daily living (IADL), 76.9% had polypharmacy (four or more medications), and 47.5% had one or more comorbidities. Median time on the Timed Up and Go was 13.3 ± 4.9 seconds. Those considered candidates for autologous stem cell transplant (N = 26) were younger, with fewer comorbidities, better performance status, and faster performance on the Timed Up and Go test. Factors independently associated with receiving autologous stem cell transplant (N = 21) included age and IADL dependence. CONCLUSION: Impairments in geriatric domains are common in this population, even among those considered to have a good performance status. Geriatric assessment domains are associated with both transplant eligibility and receipt. J Am Geriatr Soc 67:987–991, 2019.